A Locally-made Scaraboid from Khallat es-Sihrij Near Tel Aphek and Its Neo-Assyrian Connection. (3rd July 2019) - Brandl, Baruch; Itach, Gilad
Abstract : A locally made scaraboid was found during excavations at Khallat es-Siḥrij, a rural site situated 5 km southeast of Tel Aphek. The scaraboid, which most probably had been owned by an Assyrian or an Aramean official, was engraved with a new variant of the symbol of the moon god, Sin of Harran. The site of Khallat es-Siḥrij is part of a well-known group of rural sites that was established in the Neo-Assyrian period in the western Samaria foothills, primarily between Tel Aphek and Tel Hadid.